ICT USE OF TEACHERS IN TEACHING ENGLISH IN VIETNAM - Huynh Ngoc Mai Kha; Pham Thi To Nhu; Tan Choon Keong (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2018)
The purpose of this case study was to understand the real use of ICT of teachers in teaching English in Vietnam. A total of 200 primary school teachers of English from 5 provinces in Vietnam took part in this study. These teachers were interviewed and asked to write reflection journals on the ICT use they had in their teaching context. The results indicated that in spite of the fact that using ICT in teaching English in Vietnam has become much more popular than before, the majority of them were still at low level users (levels 2-3) according to Lin, Wang and Lin’s pedagogy * technology model (2012) for ICT integration in education. The study also mentioned factors that influenced the use of ICT and pointed out recommendations to push up the use of ICT among teachers of English in Vietnam.